2021
DOI: 10.1007/s11869-021-01070-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of particulate matter and identification of emission sources in Greater Caracas, Venezuela

Abstract: Between June and September 2018, particulate matter (PM) samples were taken in the Sartenejas Valley, southeast of Greater Caracas, Venezuela. The aim was to evaluate the morphology and the elemental chemical composition of particulate matter and establish possible emission sources during the rainy season. Functional groups were identified by FTIR spectroscopic analysis, and morphology and elemental composition were obtained by SEM–EDX analysis. The sampling period coincided with a Sahara dust storm. The SEM–E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Tb, Ni, Cu, Mn, Cd, and Cr were found to have the least proportion in the scanned particles. Ni, Mn, Cd and Cr have been found to have industrial origin [ 34 ].Tb has been found to be associated with very few commercial uses. It is utilized in manufacturing fluorescent lights, as a doping agent (sodium terbium borate, Na 2.67 Tb 2.11 B 3 O 9 ) in solid-state devices, and use of its alloy in manufacturing of electronic devices [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tb, Ni, Cu, Mn, Cd, and Cr were found to have the least proportion in the scanned particles. Ni, Mn, Cd and Cr have been found to have industrial origin [ 34 ].Tb has been found to be associated with very few commercial uses. It is utilized in manufacturing fluorescent lights, as a doping agent (sodium terbium borate, Na 2.67 Tb 2.11 B 3 O 9 ) in solid-state devices, and use of its alloy in manufacturing of electronic devices [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…15 Our study raises many opportunities for future research, in terms of both the development of research methods and the identification of clinically relevant pathways leading to skin damage. In addition, chloride particles were identified in KCl form, usually associated with biomass burning emissions; (b) irregular Ca carbonate particles (L: 14.37 μm and W:8.37 μm), emitted from the construction of roads, houses and buildings; (c) irregular Na-aluminosilicate particle (L:21.87 μm and W: 20.57 μm), a common constituent of soil sediments, usually associated with emissions from agricultural activities, fuel combustion and biomass burning; (d) irregular quartz-like particles, a common constituent of soil, but also found in building materials such as ceramic, cement, glass, bricks and clays; (e) tarballs from biomass burning 10,11 with high carbon elemental composition and typical spherical morphology and (f) irregular Fe-Ni-rich particles. The dominant metalliferous airborne particles are Fe, Ni, Cr and Zn-rich particles.…”
Section: Discussionmentioning
confidence: 99%
“…A large part of the particles identified, including tar balls and K-chlorides, could be attributed exclusively to ambient air pollution sources. 11,12,14 Both epidemiological and experimental studies have demonstrated a connection between AP exposure and skin disorders, including atopic dermatitis, acne, premature skin ageing and skin cancers( [1][2][3]5,11,15 The present understanding of the effects of AP on the skin is incomplete. With the exception of a few hazardous substances, data on the skin and systemic toxicity of most air pollutants are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of emissions may be a major reason for the scarcity of source apportionment studies in South America. While the application of attribution methods based on state-of-the-art chemical transport models is common in the US and Europe [ 21 ], the few previous studies that have analyzed the origin of ambient pollution levels in this region are based either on receptor models, such as the Positive Matrix Factor method [ 27 , 28 ], or statistical approaches, such as Principal Component Analysis [ 29 ]. All these studies relied on ad-hoc measurements and were limited to PM or some of its components.…”
Section: Introductionmentioning
confidence: 99%